CLUSTER ARCHITECTURAL- PLANNING ORGANIZATION OF THERAPEUTIC-REHABILITATION GARDENS: PRINCIPLES, LAYOUT MODELS AND PHYTOMODULES - Chemakina, Oktyabryna; Movchan, Valentyna; Shostak, Liubov; Gnatiuk, Liliia (Theory and practice of design, 2025)
Purpose. The article aims to develop and test a cluster-based architectural and planning model of a therapeutic and rehabilitation garden for university and medico-social environments. The cluster is considered as a basic unit of spatial organization with a hierarchy “core – intermediate clusters – periphery”, which ensures therapeutic effectiveness, accessibility and environmental legibility. Methodology. The research employs theoretical modelling and applied design analysis. The principles of universal and multisensory design and functional zoning are systematized. A typology of zones by target effects and sensory channels is proposed, as well as a standardized “passport” of the therapeutic phytomodule (purpose, species composition, conditions of placement and maintenance). Four territorial layout models are compared, and the applicability of the model is assessed through expert judgments and scenario modelling of user trajectories. Results. The hierarchy of clusters and their linkage to the routing and planning framework of the garden are substantiated, which makes it possible to construct sequences of use such as “entrance – adaptation – immersion – relaxation – reflection”. Key zones are identified (sensory, cognitive, art, rehabilitation, emotional and ecological clusters), and the structure of the phytomodule is standardized as the smallest design unit with reproducible quality. Scientific novelty. A holistic cluster model of a therapeutic garden is proposed, with detailing down to the level of the phytomodule, and the relationship between the cluster structure and the multisensory organization of space is demonstrated. Practical relevance. The model can serve as a basis for designing veteran and university therapeutic gardens and sensory routes of campuses. The modularity of the cluster approach reduces implementation costs and allows the adaptation of solutions to different urban planning conditions.